Individual Variation Does Not Regulate Foraging Response to Humidity in Harvester Ant Colonies - Nova, Nicole; Pagliara, Renato; Gordon, Deborah M. (Frontiers in Ecology and Evolution, 2022)
Differences among groups in collective behavior may arise from responses that all group members share, or instead from differences in the distribution of individuals of particular types. We examined whether the collective regulation of foraging behavior in colonies of the desert red harvester ant (Pogonomyrmex barbatus) depends on individual differences among foragers. Foragers lose water while searching for seeds in hot, dry conditions, so colonies regulate foraging activity in response to humidity. In the summer, foraging activity begins in the early morning when humidity is high, and ends at midday when humidity is low. We investigated whether individual foragers within a colony differ in the decision whether to leave the nest on their next foraging trip as humidity decreases, by tracking the foraging trips of marked individuals. We found that individuals did not differ in response to current humidity. No ants were consistently more likely than others to stop foraging when humidity is low. Each day there is a skewed distribution of trip number: only a few individuals make many trips, but most individuals make few trips. We found that from one day to the next, individual foragers do not show any consistent tendency to make a similar number of trips. These results suggest that the differences among colonies in response to humidity, found in previous work, are due to behavioral responses to current humidity that all workers in a colony share, rather than to the distribution within a colony of foragers that differ in response.